2006
DOI: 10.1007/s11205-005-3107-0
|View full text |Cite
|
Sign up to set email alerts
|

Does Wealth Enhance Life Satisfaction for People Who are Materially Deprived? Exploring the Association among the Orang asli of Peninsular Malaysia

Abstract: indigenous, poverty, satisfaction with life scale, subjective well-being, wealth,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 39 publications
(28 reference statements)
2
23
0
Order By: Relevance
“…These data are further supported by the parameter estimates of the CFAs, and is generally consistent with previous work showing that local versions of the SWLS has high internal consistency (e.g., Arrindell et al 1999;Gouveia et al in press;Hultell and Gustavsson 2008;Oishi 2006;Wu and Yao 2006). Our finding of high internal consistency also stands in contrast to the work of Howell et al (2006), who reported that the SWLS (in question-format) had low internal reliability among an Orang Asli sample in Peninsular Malaysia.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These data are further supported by the parameter estimates of the CFAs, and is generally consistent with previous work showing that local versions of the SWLS has high internal consistency (e.g., Arrindell et al 1999;Gouveia et al in press;Hultell and Gustavsson 2008;Oishi 2006;Wu and Yao 2006). Our finding of high internal consistency also stands in contrast to the work of Howell et al (2006), who reported that the SWLS (in question-format) had low internal reliability among an Orang Asli sample in Peninsular Malaysia.…”
Section: Discussionsupporting
confidence: 92%
“…The suboptimal internal consistency reported by Howell et al (2006), however, was likely caused by factors specific to their sample and difficulties with their translation of the SWLS. Specifically, their sample of Orang Asli had a very low level of formal education (which is not representative of urban, or even, non-tribal rural groups in Malaysia), may not have been fluent in Bahasa Malaysia (Malay), and may have been unfamiliar with the methods of psychological testing.…”
Section: Life Satisfaction In Malaysiamentioning
confidence: 94%
See 2 more Smart Citations
“…Böhnke and Delhey 1999a;Böhnke 2005;Møller 2007). There are also examples where smaller lists of items have been used as proxies for wealth (Howell et al 2005). 6 In fact there is one example (Böhnke and Delhey 1999b), where an indicator for deprivation based poverty and income are both included in a multivariate model explaining satisfaction with the standard of living as well as satisfaction with some other life domains.…”
Section: Materials Situation and Happiness: The Use Of Alternative Metmentioning
confidence: 99%